Shifts in metabolomic profiles of the parasitoid Nasonia vitripennis associated with elevated cold tolerance induced by the parasitoid's diapause, host diapause and host diet augmented with proline. (August 2015) - Li, Yuyan; Zhang, Lisheng; Chen, Hongyin; Koštál, Vladimir; Simek, Petr; Moos, Martin; Denlinger, David L.
Abstract: The ectoparasitoid wasp, Nasonia vitripennis can enhance its cold tolerance by exploiting a maternally-induced larval diapause. A simple manipulation of the fly host diapause status and supplementation of the host diet with proline also dramatically increase cold tolerance in the parasitoid. In this study, we used a metabolomics approach to define alterations in metabolite profiles of N. vitripennis caused by diapause in the parasitoid, diapause of the host, and augmentation of the host's diet with proline. Metabolic profiles of diapausing and nondiapausing parasitoid were significantly differentiated, with pronounced distinctions in levels of multiple cryoprotectants, amino acids, and carbohydrates. The dynamic nature of diapause was underscored by a shift in the wasp's metabolomic profile as the duration of diapause increased, a feature especially evident for increased concentrations of a suite of cryoprotectants. Metabolic pathways involved in amino acid and carbohydrate metabolism were distinctly enriched during diapause in the parasitoid. Host diapause status also elicited a pronounced effect on metabolic signatures of the parasitoid, noted by higher cryoprotectants and elevated compounds derived from glycolysis. Proline supplementation of the host diet did not translate directly into elevated proline in the parasitoid but resulted in an alteration in the abundance of many other metabolites, including elevated concentrations of essential amino acids, and reduction in metabolites linked to energy utilization, lipid and amino acid metabolism. Thus, the enhanced cold tolerance of N. vitripennis associated with proline augmentation of the host diet appears to be an indirect effect caused by the metabolic perturbations associated with diet supplementation. Graphical abstract: Highlights: Metabolomic profiles of diapausing and nondiapausing parasitoids were distinct. Host diapause status elicited a pronounced effect on the metabolic signature of the parasitoid. Augmenting the host diet with proline, exerted an indirect effect on the parasitoid's metabolomic profile.